Covid-19 pandemic and social exclusion in Kano Metropolis: challenges and the prospects - Aminu Zubairu Surajo (International Ecsis Association, 2022)
The paper focuses on the challenges of the COVID-19 pandemic on socially excluded individuals in Kano metropolis, Nigeria. People that face the risk of social exclusion comprise women and girls; people with disabilities; ethnic and religious minorities; migrants and internally displaced people; children and older people; sexual minorities and people living with HIV/AIDS. These categories of individuals are undergoing unparalleled challenges due to COVID-19 pandemic. They are all affected by the coronavirus, regardless of their social level, gender, or color. The epidemic triggered social and economic crises, exacerbating these people's already significant unemployment, poverty, and criminal activities. The study looks at the pandemic's issues as well as long-term solutions for dealing with the virus. The data was collected using a mixed technique approach. Questionnaires and in-depth interviews were used in this process. As a result, the study was guided by two hypotheses and three research questions. The study included 384 individuals, who were chosen for the questionnaire using a simple random sample technique. In a similar vein, 12 people took part in an interview. Purposive sampling was used by the researcher to identify participants for the study. According to the study's findings, there is a link between the challenges of COVID-19 epidemic and the danger of social exclusion. Family problems, anxiety, peer-group violence, child abuse, disruption of social and religious life, unemployment, poverty, inflation, and travel limitations are among the pandemic's challenges for socially excluded persons, according to the findings.